ANALISIS PELAKSANAAN KEBIJAKAN PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 DI SMA BAKTI SETIA NANGA PINOH KABUPATEN MELAWI - Ason Ason; Asep Eka Nugraha; Septian Peterianus (STKIP Pesisir Selatan, 2022)
The research was motivated by the issue of the implementation of learning during the Covid-19 pandemic period. The research was conducted with regard to the learning policy during the Covid-19 pandemic period. This research is located at Bhakti Setia Senior High School by using qualitative research methods. Data sources were obtained from the principal, curriculum field teachers, and subject teachers. Research instruments include observation sheets, interview sheets and documentation. Data collection through observation, interviews and documentation. Data analysis includes data reduction, data presentation and conclusion withdrawal. The results showed that the implementation of learning policies was carried out flexibly in two ways, namely in tissue and outside the network. The problems faced by teachers, students and parents of students in online learning are constrained by technology, not all students have gadget and the internet then the teacher's strategy in overcoming online learning problems is to use digital media with computer programs and software while luring learning is carried out with limited face-to-face-to-face learning, besides the supporting factors in the process of implementing online learning and luring, namely school management good as well as in the implementation of learning, the teacher plans the implementation of online learning and luring with planned. Based on research findings it can be concluded that the implementation of online learning policies during the Covid-19 pandemic period is effective and supported by effective school management.